2019
DOI: 10.1001/jamanetworkopen.2019.6673
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Bedside Risk Assessment for Sustained Prescription Opioid Use After Surgery

Abstract: Key Points Question Can a risk score for sustained prescription opioid use after surgery be developed for a working-age population using readily available clinical information? Findings In this case-control study of 86 356 patients undergoing 1 of 10 common surgical procedures, prior opioid exposure was the factor most strongly associated with sustained opioid use. The group with the lowest Stopping Opioids After Surgery scores (<31) had a mean 4.1% risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 26 publications
(201 reference statements)
3
81
0
1
Order By: Relevance
“…We derived the risk score's points by comparing the β coefficient of the variable to the overall sum of coefficients in the model, multiplying by 100, and rounding to the nearest integer. 26 The risk score calculated for each patient represented the summed point totals from all variables present, where a higher score indicates more suitability for discharge.…”
Section: Discussionmentioning
confidence: 99%
“…We derived the risk score's points by comparing the β coefficient of the variable to the overall sum of coefficients in the model, multiplying by 100, and rounding to the nearest integer. 26 The risk score calculated for each patient represented the summed point totals from all variables present, where a higher score indicates more suitability for discharge.…”
Section: Discussionmentioning
confidence: 99%
“… Abbreviation: SOS, Stopping Opioids After Surgery. a Adapted from Chaudhary et al 81 b Defined as officer sponsor rank, proxy for high economic status. c Defined as enlisted sponsor rank, proxy for low socioeconomic status. d Appendectomy, inguinal herniorrhaphy, transurethral resection of prostate. e Requires access to major organ spaces or osseous resection, including colectomy, coronary artery bypass graft, nephrectomy, radical cystectomy, total knee arthroplasty, total hip arthroplasty, and hip fracture repair. f ≥6 months of continuous prescription without interruption exceeding 7 days. …”
Section: Key Action Statementsmentioning
confidence: 99%
“…Several studies focused on identifying risk factors that predispose patients to this opioid dependency. Some studies found that performing instrumented spinal fusion was one of the leading risk factors that predicted prolonged opioid prescriptions in opioid-naive patients [ 26 , 27 , 28 ]. Moreover, Schoenfeld et al showed that low-intensity surgical procedures were associated with a higher likelihood of discontinuing opioid use [ 29 ].…”
Section: Discussionmentioning
confidence: 99%